Monte Carlo dosing simulations of topical terpinen-4-ol from Zingiber cassumunar oil against Cutibacterium acnes and Staphylococcus aureus - Win, Ei Ei; Chooluck, Kotchaphan; Nosoongnoen, Wichit (Science, Engineering and Health Studies, 2025)
Plai oil is an essential oil derived from the steam distillation of Zingiber cassumunar rhizome. The oil contains terpinen-4-ol (T4) as its major component. This study developed and validated gas chromatographic–mass spectrometric methods for quantifying and investigating the physicochemical properties of T4 and determined the effective dosage regimens of T4 against Cutibacterium acnes and Staphylococcus aureus using Monte Carlo simulation. The results demonstrated that the aqueous solubility of pure T4 was higher than that of T4 in plai oil, and the log Kow of T4 in the pure form and plai oil were in the ranges of 0.73–2.83 and 0.77–2.88, respectively. The simulation analysis suggested topical pure T4 dosage regimens of 1.50 and 2.00 g/cm2 every 12 h to suppress C. acnes (MIC 1,489.60 µg/mL) and S. aureus (MIC 2,327.50 µg/mL), respectively, to achieve the PKPD targets of Cmax > MIC and AUC > 2×MIC. When converted to plai oil (21.23% w/w of T4), the topical dosage regimens were 7.07 and 9.42 g/cm2 every 12 h, respectively. At higher MIC or PKPD targets, the topical dosage regimens of T4 and plai oil were 2.70 and 12.72 g/cm2 for C. acnes and 3.00 and 14.13 g/cm2 for S. aureus, every 12 h.